Do overall dimension ratings from assessment centres show external construct-related validity?. Issue 3 (3rd May 2020) - Wirz, Andreja; Melchers, Klaus G.; Kleinmann, Martin; Lievens, Filip; Annen, Hubert; Blum, Urs; Ingold, Pia V.
ABSTRACT: There have been repeated calls for an external construct validation approach to advance our understanding of the construct-related validity of assessment centre dimension ratings beyond existing internal construct-related validity findings. Following an external construct validation approach, we examined whether linking assessment centre overall dimension ratings to ratings of the same dimensions that stem from sources external to the assessment centre provides evidence for construct-related validity of assessment centre ratings. We used data from one laboratory assessment centre sample and two field samples. External ratings of the same dimensions stemmed from assessees, assessees' supervisors, and customers. Results converged across all three samples and showed that different dimension-same source correlations within the assessment centres were larger than same dimension-different source correlations. Moreover, confirmatory factor analyses revealed source factors but no dimension factors in the latent factor structure of overall dimension ratings from the assessment centre and from external sources. Hence, consistent results across the three samples provide no support that assessment centre overall dimension ratings and ratings of the same dimensions from other sources can be attributed to dimension factors. This questions arguments that assessment centre overall dimension ratings should have construct-related validity.